Sosialisasi Penggunaan Media Pembelajaran Berbasis WEBS Dalam Pembelajaran ESP - Syakur, Abd.; Susilo, Tri Achmad Budi; Mubarok, M. Khusni; Riza, Moch. Dicky; Damyati, Akhmad Rofii (Indonesian Journal Publisher, 2023)
Education has many elements and dimensions that refer to learning media as a determining factor for the success of learning activities. The use of media in its implementation, of course, has the aim of helping the learning process run more optimally and structured. The media determines the success or failure of the learning process. ESP learning at Al Mujtama Pamekasan Islamic High School, needs to be developed using Website-based learning media. The implementation of this service applied the Participatory Action Research (PAR) method and model. This activity lasted for three days, namely on 4, 5 and 6 April 2022 which was carried out offline with theoretical and practical concepts to all lecturers at STAI Al Mujtama.Pamekasan. There were some activities done covering the introduction, delivery of service stages, and socialization of the use of Webs-based ESP learning media. The results obtained from this service, namely lecturers are able to convey subject matter well, lecturers are easier to convey material to students, improve the quality of learning outcomes, learning is more directed, learning is more concrete and feels better understood. Internal audits are conducted twice per semester by stakeholders affiliated with the Quality Assurance Institution (LPM). This is done as a way to control the performance of teachers at Madrasah Al Mujtama Pamekasan. It is hoped that the next service will be developed in the development of very relevant materials and outputs in the form of the English for Specific Purposes (ESP) book according to the knowledge at STAI Al Mujtama Pamekasan.